EVALUATION OF NEUROPROTECTIVE EFFECT OF AZILSARTAN AS MEMORY ENHANCER AGAINST SCOPOLAMINE AND SODIUM NITRITE-INDUCED AMNESIA IN SWISS ALBINO MALE RATS - THAKUR, CHANCHAL; ASHWLAYAN, VRISH DHWAJ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to assess the neuroprotective effect of azilsartan as a memory enhancer against scopolamine-induced amnesia in rats. Methods: Albino Swiss male rats in equal numbers per group (n=6) were taken. Scopolamine hydrobromide was administered to induce amnesia within the rats. Control group rats were administered normal, negative control groups were administered with scopolamine to induce amnesia and nitrite during trials, positive control group rats were administered piracetam+ scopolamine and piracetam nitrite during trials, and test control group rats were administered azilsartan +sodium nitrite and azilsartan nitrite. Exteroceptive behavioral models just like the elevated plus-maze model, Morris water maze model, acquisition trials, and retrieval trial were wont to evaluate the neuroprotective effect of azilsartan. Results: The scopolamine and azilsartan have a significantly decreasing effect on time spent within the target quadrant (TSTQ) but piracetam has an increasing effect. The effect of azilsartan on transfer latency time (TLT) was observed against scopolamine-induced amnesia in rats using the elevated plus-maze test. Piracetam was found to decrease the TLT and restore memory function at a better dose. Within the case of scopolamine treated rats, a big increase in TLT was noted. Azilsartan treated group also increased TLT within the elevated plus maze. It is noted that the scopolamine features a significantly increasing effect on escape latency time (ELT). Piracetam features a decreasing effect on ELT. A rise in ELT was seen because of azilsartan. Conclusion: This study suggested that the azilsartan features a significant decreasing effect on TSTQ, azilsartan treated group also increased TLT and ELT.